A Review Article: Free Radical and Replacement Synthetic Antioxidant by Natural Antioxidant - Shoker, Roaa M. H.; Al-Shammery, Wasan Hamza; Al-Aidy, S. R. (Journal for Research in Applied Sciences and Biotechnology, 2023)
Free radical may be responsible of several pathophysiology disease for threatening human life, and they are produced from endogenous and exogenous sources. Using the balanced amount of nutritious diet lead to a good health, may be neutralizing or scavenging free radicals by antioxidants compounds. daily diet have large number of vitamin A, E and C, carotenoids, polyphenols, etc. as natural antioxidants, the main bases of them are fruits, cereals, vegetables, and beverages. Enzymatic and non-enzymatic antioxidant substances are two different kinds that lessen the reactions of free radicals. In order to protect itself from reactive oxygen species, the human body uses an enzyme antioxidant. The two kinds of non-enzymatic antioxidants are natural antioxidants and synthetic antioxidants. The aim of this review is to knowledge a reasons which causes the free radical and balance them by natural antioxidant constituents, and replacement synthetic antioxidant by natural antioxidant, due to daily diet have large amounts from natural antioxidants, and natural antioxidants more effective than synthetic antioxidants, in additional they occurrence in nature and more inexpensive.